Young Children's Comprehension of Temporal Relations in Complex Sentences: The Influence of Memory on Performance. Issue 6 (26th August 2015) - Blything, Liam P.; Davies, Robert; Cain, Kate
Abstract : The present study investigated 3‐ to 7‐year‐olds' ( N  =   91) comprehension of two‐clause sentences containing the temporal connectives before or after . The youngest children used an order of mention strategy to interpret the relation between clauses: They were more accurate when the presentation order matched the chronological order of events: "He ate his lunch, before he played in the garden" (chronological) versus "Before he played in the garden, he ate his lunch" (reverse). Between 4 and 6 years, performance was influenced by a combination of factors that influenced processing load: connective type and presentation order. An independent measure of working memory was predictive of performance. The study concludes that the memory demands of some sentence structures limits young children's comprehension of sentences containing temporal connectives.